Monochromatic subdiffusive spatial frequency domain imaging provides in‐situ sensitivity to intratumoral morphological heterogeneity in a murine model. Issue 2 (3rd November 2016) - McClatchy, David M.; Hoopes, P. Jack; Pogue, Brian W.; Kanick, Stephen Chad
Abstract : For the first time, spatially resolved quantitative metrics of light scattering recovered with sub‐diffusive spatial frequency domain imaging (sd‐SFDI) are shown to be sensitive to changes in intratumoral morphology and viability by direct comparison to histopathological analysis. Two freshly excised subcutaneous murine tumor cross‐sections were measured with sd‐SFDI, and recovered optical scatter parameter maps were co‐registered to whole mount histology. Unique clustering of the optical scatter parameters μ s ′ vs. γ (i.e. diffuse scattering vs. relative backscattering) evaluated at a single wavelength showed complete separation between regions of viable tumor, aggresive tumor with stromal growth, varying levels of necrotic tumor, and also peritumor muscle. The results suggest that with further technical development, sd‐SFDI may represent a non‐destructive screening tool for analysis of excised tissue or a non‐invasive approach to investigate suspicious lesions without the need for exogenous labels or spectrally resolved imaging. Abstract : Histopathology remains the gold standard for evaluating in‐situ tissue morphology. But with the processing needed to make a histology slide, real time microscopic assessment of resected tissues remains difficult. In this manuscript, a new wide‐field imaging technique has shown sensitivity to morphological changes in murine tumors, through spatially resolved measurements of superficial light scattering. With future developments, this technique could be a promising modality for real‐time characterization of resected tissues.